2014
DOI: 10.1140/epjc/s10052-014-2869-4
|View full text |Cite
|
Sign up to set email alerts
|

Accretions of various types of dark energies onto Morris–Thorne wormhole

Abstract: In this work, we have studied the accretion of dark energies onto a Morris-Thorne wormhole. Previously, in ref. (González-Díaz, arXiv:hep-th/0607137), it was shown that for quintessence like dark energy, the mass of the wormhole decreases, and for phantom like dark energy, the mass of the wormhole increases. We have assumed two types of dark energy: the variable modified Chaplygin gas and the generalized cosmic Chaplygin gas. We have found the expression of the wormhole mass in both cases. We have found the ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 72 publications
(96 reference statements)
1
9
0
Order By: Relevance
“…Hence, our observation that the holographic dark energies, when accreting on wormhole, leading to an increase in the wormhole mass in the phantom phase of the universe is in agreement with [61]. Also, the study is in agreement with [18], who showed that accretion of two types of Chaplygin gas onto Morris-Thorne Wormhole lead to increase in wormhole mass in the phantom phase of the universe. …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Hence, our observation that the holographic dark energies, when accreting on wormhole, leading to an increase in the wormhole mass in the phantom phase of the universe is in agreement with [61]. Also, the study is in agreement with [18], who showed that accretion of two types of Chaplygin gas onto Morris-Thorne Wormhole lead to increase in wormhole mass in the phantom phase of the universe. …”
Section: Discussionsupporting
confidence: 89%
“…They inspired from the quantum effects [26,27]. Different aspects of wormholes are widely studied in literature from general relativity to modified gravities [18]- [21]. Wormholes can be immersed in in a FriedmannLemaitreRobertson Walker (FLRW) universe [16,28,29].…”
mentioning
confidence: 99%
“…Later on, Michel [19] analyzed the accretion process of a steady-state spherically symmetric flow of matter into a compact object. Consequently, several authors studied accretion process of various kinds of matter onto different types of black holes [20][21][22][23][24][25][26][27][28][29][30][31][32][33] and wormholes [34][35][36][37][38][39][40]. We should clarify that we are considering matter flow on the background of EBWH assuming that the Einstein minimally coupled scalar field φ has entirely gone into building the background EBWH geometry and that matter is flowing on top of that geometry.…”
Section: Introductionmentioning
confidence: 99%
“…If dark energy accretes onto the BTZ BH, the rate of change of the mass of the black hole is expressed in terms of the density and pressure of dark energy and also we find the expression of the BH mass in terms of the density. In our previous work, we have investigated accretions of various types of dark energies (including some kinds of parametrizations of dark energy) onto a Morris-Thorne wormhole [59]. Our main motivation for this work is to examine the natures of the mass of the black hole during the accelerating expansion of the FRW universe if several kinds of dark energies accrete around the BH.…”
Section: Introductionmentioning
confidence: 99%